PHYSICAL PROPERTIES AND INTERNAL STRUCTURE OF GREENLAND SNOW. - Nakaya,Ukichiro; Kuroiwa,Daisuke (1970)
Experiments were carried out near Thule, Greenland, on the correlation between the physical properties and internal structure of snow. About 150 snow samples obtained to 26 m depth were measured for elastic modulus, air permeability, unconfined compressive strength, static compression and creep. The observed density profile curve deviated from the theoretical curve at a depth of 10 m. and density of 0.52 g/cu cm, a value almost equivalent to the limiting density obtainable by simple mechanical packing. Therefore, further densification must proceed through plastic flow in grains. A similar critical depth was observed in the vertical distribution of Young's modulus. A positive correlation was found between Young's modulus and an adverse correlation between average grain diameter and Young's modulus or density. There were reciprocal correlations between air permeability and density or unconfined compressive strength, and between the number of grains and their average diameters. Kozeny's constant of Greenland snow was obtained from air permeability values and the length of peripheries of cross sections of grains. To demonstrate the change of internal structure of snow due to densification, static compression tests of snow cylinders were conducted, and thin sections of snow texture were compared before and after compression. (Author)